Patterns of peripheral cytokine expression during pregnancy in two cohorts and associations with inflammatory markers in cord blood. (12th September 2016) - Ross, Kharah MacKenzie; Miller, Gregory; Culhane, Jennifer; Grobman, William; Simhan, Hyagriv N.; Wadhwa, Pathik D.; Williamson, Douglas; McDade, Thomas; Buss, Claudia; Entringer, Sonja; Adam, Emma; Qadir, Sameen; et al.
Abstract : Problem: Maternal inflammation undergoes adaptations during pregnancy, and excessive inflammation has been associated with adverse outcomes. One mechanism may be maternal inflammation transmission to the fetal compartment. Links between maternal pregnancy inflammation and fetal inflammation are poorly characterized. Method: Principal components analysis was used to extract underlying inflammation components across cytokines (IFN‐γ, IL‐10, IL‐13, IL‐6, IL‐8, TNF‐α) in two pregnancy cohorts (SPAH N=87, MOMS N=539) assessed during the second and third trimesters. Links between maternal inflammation over pregnancy and fetal (cord blood) inflammation were assessed. Results: Substantial cytokine rank‐order stability was observed in both cohorts, β's range .47‐.96, P 's <.001. Two consistent inflammatory components were extracted: a pro‐inflammatory (IL‐10, IL‐6, IL‐8, TNF‐α, IFN‐γ) component and anti‐inflammatory (IL‐13) component. Higher maternal pro‐inflammatory and lower anti‐inflammatory indices during pregnancy were associated with higher cord blood inflammation, P 's>.04. Conclusion: Maternal inflammation indices over pregnancy were associated with inflammation in cord blood at birth. Results have implications for understanding pregnancy inflammatory processes and how maternal inflammation may be transmitted to fetal circulation.